The relationship between client attachment and therapist interventions in client-nominated relationship building incidents - Janzen, Jennifer I.; Fitzpatrick, Marilyn R.; Drapeau, Martin; Blake, Emily (Canadian Journal of Counselling and Psychotherapy, 2010)
Résumé Vingt-quatre clients ont été invités à nommer un incident qui était critique au développement de leur rapport thérapeutique avec un thérapeute de stagiaire. Les résultats de la régression multiple ont indiqué que l'inquiétude d'attachement a modéré le rapport entre l'action d'éviter d'attachement et le type d'interventions de thérapeute actuelles dans le RBI. Les clients qui a basse inquiétude et basse action d'éviter a nommés incidents avec des niveaux plus élevés des interventions exploratoires. Les clients qui ont basse inquiétude et action d'éviter élevée ont nommé des incidents avec des niveaux plus élevés des interventions de support. Abstract Twenty-four clients were asked to nominate an incident that was critical to the development of their therapeutic relationship with a trainee therapist. Therapist interventions within each client relationship building incident (RBI) were identified. The results of multiple regression indicated that attachment anxiety moderated the relationship between attachment avoidance and type of therapist interventions present in the RBI. Secure clients (low anxiety, low avoidance) nominated incidents with higher levels of exploratory interventions. Dismissing clients (low anxiety, high avoidance) nominated incidents with higher levels of supportive interventions. Issues related to tailoring therapist behaviours to client attachment style to facilitate positive alliances are discussed.